Measuring Pragmatism in Islamic Economic Practice in Southeast Asia - Muhammad Helmi Falah; Fety Widianti Aptasari (Jurnal Ilmiah Ekonomi Islam, 2026)
This study aims to examine the foundation for the application of Islamic economics and sustainable development based on Islamic principles in Southeast Asian countries, focusing on three nations recognized among the top 15 in implementing Islamic economics. The Southeast Asian region is highly diverse in terms of economic structure, populism, public education, and government systems. The paper highlights anomalies and pragmatic practices in Islamic economics. Pragmatism in Islamic economic practices is often found among lower- to middle-income groups with limited education, who perceive that the costs (margins) charged by Islamic financial institutions are higher than those of conventional ones. At the national level, Islamic economic pragmatism is reflected in its use as a tool for diplomacy and international economic cooperation. Findings show that all three countries face similar challenges of low inclusiveness in Islamic economic-based development. However, they show positive trends in economic stability due to diversification. In terms of environmental sustainability, Singapore leads in eco-friendly innovation, Malaysia has established a sharia-compliant carbon market, while Indonesia continues to face complex environmental issues. Regarding social sustainability, all three countries share the common issue of high socio-economic inequality.